FAKTOR FAKTOR YANG BERPENGARUH TERHADAP AUDIT DELAY PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2013)
The company's financial statements as a form of responsibility towards the stakeholders who have invested their capital to the company. Timeliness of financial reports is very important for the stakeholders to know the actual circumstances of the company in making timely and accurate decisions and helps them to reduce asymmetric information. The term itself means to delay the audit delay submission of financial statements to the public because of the presence of the audit process is calculated by summing the days between the date of per - period financial statements published by the company up to the date of the audit report issued by an independent auditor. This study aims to analyze the factors that influence audit delay on food and beverages companies listed in Indonesia Stock Exchange. The variables used for this study were the size of the firm, the public accounting firm size, profitability, solvency and extraordinary items. The data used are secondary data obtained in the financial report Indonesia Stock Exchange (www.idx.co.id), and the data ICMD (Indonesian Capital Market Directory). The analytical method used is multiple regression analysis. Based on the survey results revealed that the average length of audit delay is on food and beverages companies in the Stock Exchange is 76 days. Independent variables simultaneously influence audit delay, but only the size of the firm which individually have a significant influence on audit delay.